2022
DOI: 10.1002/slct.202201237
|View full text |Cite
|
Sign up to set email alerts
|

Evolution Process of Humins Derived from Glucose

Abstract: The evolution process of humins derived from glucose was studied dynamically from the feedstock, the intermediates in solution, till humins solid formed. The key intermediates resulting in the formation of humins were identified, unveiling two elementary reactions including etherification of dehydrated glucose and electrophilic substitution of furfuryl alcohol (FAL). The characteristic IR peaks at 1583 and 1616 cm−1 could be attributed to the C=C conjugated with C=C and the C=C conjugated with C=O, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
2
3
0
Order By: Relevance
“…These signals could be assigned to the CC stretching vibration conjugated with carbonyl at 1600 cm −1 and the CO stretching vibration at 1700 cm −1 . 21,30 The described development of the signals is consistent with the formation mechanisms of humins postulated in the literature. 16,17,21,30,31 Accordingly, glucose dehydrates under acid catalysis in the first step to 5-hydroxymethylfurfural (5-HMF), which reacts further to obtain levulinic acid (LeA) under ring opening.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…These signals could be assigned to the CC stretching vibration conjugated with carbonyl at 1600 cm −1 and the CO stretching vibration at 1700 cm −1 . 21,30 The described development of the signals is consistent with the formation mechanisms of humins postulated in the literature. 16,17,21,30,31 Accordingly, glucose dehydrates under acid catalysis in the first step to 5-hydroxymethylfurfural (5-HMF), which reacts further to obtain levulinic acid (LeA) under ring opening.…”
Section: Resultssupporting
confidence: 85%
“…21,30 The described development of the signals is consistent with the formation mechanisms of humins postulated in the literature. 16,17,21,30,31 Accordingly, glucose dehydrates under acid catalysis in the first step to 5-hydroxymethylfurfural (5-HMF), which reacts further to obtain levulinic acid (LeA) under ring opening. In the studies by Wassenberg et al , 21 both intermediates were detected as part of the liquid reaction phase of the acid-catalyzed conversion of hexoses.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…In our previous studies, we reported the formation of HMF and glucose-derived humins via a small-molecule mechanism. , In the present study, we report the fabrication of chitosan-derived humins by catalysis of weak acids via oligomer mechanism. The weak acids, such as OA and HOAc (Supporting Information, Figure S1), can only catalyze chitosan to obtain oligomers, whereas glucosamine monomer cannot be detected by NMR or HPLC.…”
Section: Discussionmentioning
confidence: 99%
“…Shen et al studied the formation mechanism of HMF-derived humins, revealing multiple elementary reactions such as etherification, esterification, aldol condensation, and acetalization . Recently, Shan et al proposed that glucose-derived humins were formed mainly through etherification of dehydrated glucose and electrophilic substitution of furfuryl alcohol . Our research demonstrated that controlling the humins structure was achievable.…”
Section: Introductionmentioning
confidence: 97%